Terceirização : violação ou concretização dos direitos humanos? - Pereira Júnior, Manoel Amaro (2012)
This assignment has as a theme Outsourcing: violation or realization of fundamental rights? . The title chosen was a result of the author s concerns, as to the modifications in which the labor relation is now passing by. The method used in this assignment, with the help of books, journals and research, was the deductive. At first, the author makes an analysis about the fundamental principles. Then, was analyzed some of actual and atypical forms of workers' hiring, due to flexible politics, with special focus on outsourcing. In the course of the study, the author will do a connection between these subjects, in an attempt of demonstrating what the outsourcing, founded in its normative instrument (Docket 331 of the Superior Court of the Work), reaches, in a negative way, principles of labor rights, making doubts with the entire protection base that stands for it. As can be seen, after many investigations, it concludes that the outsourcing, legally approved by the state, through the highest work court of the country, is against constitutional principles for the workers, as the jus fundamental rights